Perancangan Video Promosi Pencak Silat Setia Hati Organisasi - Benny Zanuarwan Putra Guchy (JURNAL INTEGRASI, 2014)
Promotional video is used as a process of personal and corporate brand. The purpose of this design is to produce a video that discusses the design of martial arts at heart loyal fraternal organization in an effort to promote martial arts organization devoted heart. The model used in this design is the design model by Fred Wibowo. Procedural design include: the process of pre-production, production and, post-production. The results of designing a promotional video of semi-documentary. With results like this design, is expected to introduce the Pencak Silat Setia Hati Organisasi the general public especially in Batam.